A LEADER-megközelítés alkalmazásának tapasztalatai az eredményesség, hatékonyság és fenntarthatóság szemszögéből - Kis, Krisztián; Nagy, Sándor (Közép-Európai Közlemények, 2012)
This paper discusses the experiences of the implementation of LEADER approach from the perspective of effectiveness, efficiency and sustainability. In the late 1980s, the EU’s rural development policy shifted towards endogenous development, as introduced into the practice of rural development in the framework of the LEADER programme. The LEADER as the new model of rural development policy, the new paradigm of development focuses on participation, cooperation and utilization of the local resources. The basic institutions of implementation of the LEADER programme are the LAGs (Local Action Groups as local partnerships), which have a great role in the local development with their proactive operation. The impact assessment of the implementation of the LEADER approach showed that in spite of several positive examples, there are many factors which hinder the wide adoption of the features of the programme into practice, thus realization of results and impacts expected from it in the process of local development. Therefore, it is absolutely necessary to maintain and strengthen the factors of success and to avoid factors which weaken or hinder the effective adaptation of the method. Thereby it can be hoped that the possibilites provided by the LEADER approach can be utilized in the local rural development.